2019
DOI: 10.1128/jvi.00851-19
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nuclear Ribonucleoprotein A1 and Lamin A/C Modulate Nucleocytoplasmic Shuttling of Avian Reovirus p17

Abstract: Avian reovirus (ARV) p17 protein continuously shuttles between the nucleus and the cytoplasm via transcription-dependent and chromosome region maintenance 1 (CRM1)-independent mechanisms. Nevertheless, whether cellular proteins modulate nucleocytoplasmic shuttling of p17 remains unknown. This is the first report that heterogeneous nuclear ribonucleoprotein (hnRNP) A1 serves as a carrier protein to modulate nucleocytoplasmic shuttling of p17. Both in vitro and in vivo studies indicated that direct interaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…ARV p17 protein interacts with hnRNPA1 and is indirectly shuttled across the nuclear pore complex, alongside the hnRNPA1‐transportin‐1 cargo . C‐terminal, glycine‐rich region (195‐268 aa) of hnRNPA1 is deemed crucial for its interaction with ARV p17 (19‐40 aa) . This is supported by site‐directed mutagenesis, wherein mutant hnRNPA1 195‐268 with intact M9 NLS (195‐268 aa) retained its binding ability to p17, whereas mutant hnRNPA1 1‐184 (1‐184 aa) lost its capacity to interact with p17, thereby leading to the nuclear accumulation of ARV p17 protein .…”
Section: Multiple Roles Of Hnrnpa1 In Virusesmentioning
confidence: 97%
See 2 more Smart Citations
“…ARV p17 protein interacts with hnRNPA1 and is indirectly shuttled across the nuclear pore complex, alongside the hnRNPA1‐transportin‐1 cargo . C‐terminal, glycine‐rich region (195‐268 aa) of hnRNPA1 is deemed crucial for its interaction with ARV p17 (19‐40 aa) . This is supported by site‐directed mutagenesis, wherein mutant hnRNPA1 195‐268 with intact M9 NLS (195‐268 aa) retained its binding ability to p17, whereas mutant hnRNPA1 1‐184 (1‐184 aa) lost its capacity to interact with p17, thereby leading to the nuclear accumulation of ARV p17 protein .…”
Section: Multiple Roles Of Hnrnpa1 In Virusesmentioning
confidence: 97%
“…Chiu et al reported that in avian reovirus (ARV) infection, nonstructural protein p17 is shuttled to and fro from the nucleus in an hnRNPA1‐dependent manner . hnRNPA1 is constantly shuttled to and fro the nucleus by an active import/export mechanism which relies on its interaction with the F‐peptide (301‐318 aa) of Transportin‐1, a member of the importin family .…”
Section: Multiple Roles Of Hnrnpa1 In Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…The interactions of N-P-L proteins form the ribonucleoprotein (RNP) complex that holds the viral RNA genome. Additionally, matrix protein performs multifunctional roles, as it acts as a nucleocytoplasmic shuttling protein (Chiu et al, 2019). It plays a regulatory role in the expression of viral and host proteins (Delmas et al, 2008) causes cytopathic effect (CPE) and induces apoptosis (Chen et al, 2010;Lin et al, 2009) even when expressed independent to other viral proteins (Gaddy & Lyles, 2005) and also leads to autophagy, thereby suppressing the anti-viral immune pathway ultimately benefiting in the virus production (Cheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, avian reovirus p17 protein has been demonstrated to function like v-CDKI, [28] which shuttles between the Fig. 5 The regulation of cells CDK and CIKs expression by HBV and HCV cytoplasm and the nucleus [128] to perform specific duties in mediating cancer cell cycle and growth [28]. Avian reovirus protein p17 is a nucleoporin Tpr Suppressor and can activate p53, p21 and PTEN and inactivates the PI3K/AKT/mTOR and ERK signaling pathways [79,129].…”
Section: Reovirusmentioning
confidence: 99%